Analisis Nilai Tambah Keripik Gedebog Pisang Industri Rumah Tangga Raffi Snack di Kabupaten Klaten - Tauhid Yan N; Setyorini, Agung; Yos Wahyu Harinta (Universitas Veteran Bangun Nusantara, 2024)
Banana stem chips are snacks with banana stem as the main raw material. The chips have been produced by Raffi Snack Home Industry (IRT) in Dengkeng Wetan Village, Wedi District, Klaten Regency. The research aimed to determine the cost, revenue, profit, and efficiency, as well as the value added of banana stem chips. The basic research method used a qualitative design with a quantitative approach. The selection of the research area was done purposive. Respondents in this study were owners and employees of IRT Raffi Snack and data analysis methods using cost analysis, revenue, profit, and efficiency, while to analyze the value added using the hayami method. The results explained that the total cost per month was Rp 901,833 with details of fixed costs of Rp 108,833 and variable costs of Rp 793,000. Total revenue was Rp 3,600,000 and profit was Rp 2,698,167. Business efficiency is shown by RC and BC Ratio. The R/C value of 3.99 and B/C of 2.99 or > 1 means that the banana stem chips business is feasible. The value added obtained in this banana stem chips amounted to Rp 131,750/kg. The value-added ratio is the percentage between the value added and the value of output, the amount of the value-added ratio in these chips is 58.56%. The value-added ratio is classified as high because it has a value-added ratio of > 40%. The profit earned amounted to Rp 109,250 with a profit ratio of 82.92.